Characterisation of selected micro-estuaries and micro-outlets in South Africa using microalgal, zooplanktonic and macrozoobenthic assemblages. Issue 4 (6th December 2019) - Magoro, ML; Dalu, T; Human, LRD; Perissinotto, R; Deyzel, SHP; Wooldridge, TH; Adams, JB; Whitfield, AK
Abstract : South Africa has approximately 200 micro-estuaries and micro-outlets along its more than 3 000 km of coastline. Many of these microsystems (i.e. micro-outlets and micro-estuaries) share some characteristics with temporarily open/closed estuaries, but differ in that they are supplied by localised catchments with limited supply of freshwater and less connectivity to the marine environment. Between 2015 and 2016 we investigated whether micro-outlets and micro-estuaries can be differentiated from each other and other estuaries based on physico-chemical properties, microalgal dynamics, as well as species diversity and composition of invertebrate communities. The micro-outlets were dominated by oligohaline or freshwater conditions, whereas micro-estuaries were mostly mesohaline. Microalgal biomass in both system types was influenced by temperature, nutrient concentration and light availability. The micro-estuaries had a higher microalgal biomass than the micro-outlets. Chironomidae and Ephemeroptera numerically dominated benthic macroinvertebrate micro-outlet communities, whereas Amphipoda and Mysida were most dominant in micro-estuaries. Calanoid copepods dominated zooplankton assemblages in micro-estuaries and macroinvertebrate larvae in micro-outlets. In addition, the zooplankton densities were significantly higher ( p < 0.05) in micro-estuaries compared with micro-outlets. Study results confirm that there are major differences between the biota in the two microsystem types, accordingly making biotic assemblages, together with physico-chemical parameters, a viable tool for differentiating between micro-estuaries and micro-outlets.